Serviam-se a fartar das nativas submissas”: gênero, etnia e colonialidade na obra de Moysés Vellinho (1964) - Lima, Pâmela Cristina de (2022)
Since I was little, I've wondered why the women in my family cooked and washed the dishes at end-of-year lunches, while most of the men remained comfortable with their cold drinks. I also wondered about the “funny” of jokes about blondes, about the advertisements of happy women next to their colorful appliances and I was indignant at not being able to ask Santa Claus for a remote control car instead of a toy kitchen or of a doll. When trying to play with my cousin's toys, I was warned that it was “a kid thing”. This all worried me. The disparities between men and women were visible to me from an early age. Later, when studying History at school and as an undergraduate, especially, I came across frames of exclusion that were often legitimized by those I saw as summarily important to the science that I love studying so much – historians. In 2018, when starting my journey in the area of ​​historical research, I read texts by authors that aroused a lot of anguish and concern in me. It took me some time to realize that my experience as a young researcher met the questions of the rosy-cheeked child that I was. Upon realizing this meeting, I sought to better understand how differences were constructed historically, navigating seas that made me want to know more and more about this topic. Thus, along the way, I came across issues involving gender, which question the fixed character of the category “woman” and which demonstrate the existing plurality. Here is the itinerary that brought me here.